THE DIFFICULTIES FACED BY UNDERGRADUATE STUDENTS OF ENGLISH LANGUAGE EDUCATION PROGRAM WHEN LEARNING “ICT IN ELT” IN ONLINE ENVIRONMENT - Nugrahani, Arina (Wakil Rektor 3, Direktorat Riset, Publikasi dan Inovasi, Universitas Teknologi Sumbawa, 2025)
Our lives have been significantly impacted by information and communication technology (ICT) which is continuously growing. Due to the spread of COVID-19, many sectors have been forced to accelerate their technological innovation. It also has had a significant impact on education throughout the world and it aroused the use of e-learning which was previously seen as a complementary medium in the education process. English language education program is program that prepares and trains future teachers, and a course called